Inovasi Perangkat Pembelajaran Berbasis TPACK pada Pembelajaran IPAS di MIM 18 Sumberrejo - Linda Ayunda; A.F. Suryaning Ati MZ; Arfian Mudayan (Mataram University, 2026)
Science learning requires innovative learning tools that utilize technology to enhance students' critical thinking skills. However, the use of learning tools in schools remains ineffective, resulting in low critical thinking skills. This research aims to develop learning tools based on Technological Pedagogical Content Knowledge (TPACK). This study used the Research and Development (R&D) method with the 4-D model (Four-D): define, design, develop, and disseminate. The research design used a control group pretest posttest. The research subjects were 21 students of class IVA as the control class and 24 students of class IVB as the experimental class at MI Muhammadiyah 18 Sumberrejo Bojonegoro. Data analysis techniques used validity, normality, homogeneity, T-test, and N-Gain Score tests. The results of the study indicate that the TPACK-based learning device is valid, practical, and effective. This is evidenced by the T-test results of 0.000 < 0.05 and the N-Gain Score results of the experimental class of 77.98% in the high category, while the control class was 50.47% in the medium category. It is concluded that the TPACK-based learning device can improve students' critical thinking skills in science learning.